Storage layout optimization with Order Oriented Slotting (OOS) and Interaction Frequency Heuristic (IFH) for improved picking efficiency: a case study at Toserba Selamat Cipanas Cianjur - Anita Ilmaniati; M. Abdee Teguh Putra (Universitas Suryakancana, 2026)
At the Toserba Selamat Cipanas Cianjur warehouse, product placement is frequently determined by the availability of empty space rather than by demand levels or inter-product relationships. This unstructured warehouse layout has consequently resulted in order fulfillment delays, averaging 6.5% of total overall orders. This study aims to propose a more optimal storage layout and product arrangement to enhance picking efficiency within the warehouse. Layout optimization was carried out through the Order Oriented Slotting (OOS) and Interaction Frequency Heuristic (IFH) approaches, applied to the medium-sized (M) Non-Food Stock Keeping Unit (SKU) category, which exhibited the highest delay rate at 20%. These methods were implemented by analyzing Work Order List (WOL) data over the period of March 2024 to March 2025, based on the frequency of occurrence and inter-product interaction. The proposed layout was redesigned by prioritizing slots closest to the Inbound/Outbound (I/O) point for high-demand and highly interactive SKUs. Implementation results demonstrated a reduction in average Cycle Time from 4.03 minutes to 1.20 minutes per WOL, representing a time efficiency improvement of 70.27%. Furthermore, all WOLs in the new layout were successfully processed without any delays. These findings confirm that the OOS–IFH method is effective in enhancing picking performance and reducing travel time through demand-data-driven slot arrangement.